DISPARITY: THREAT OR OPPORTUNITY TO DISTANCE EDUCATION THROUGHPUT AT THE SOUTH AFRICAN MILITARY ACADEMY - Khoza, Lindiwe; van Zyl, Gerhard (Scientia Militaria - South African Journal of Military Studies, 2015)
Improved student throughput remains on the South African Higher Education (HE) priority list. To achieve greater throughput, all institutions of higher learning need to contribute. The South African Military Academy offers distance education (DE) programmes to employees of the South African Department of Defence (DoD). Its distance education (DE) programme, earmarked to become the main HE provider to the DoD, compared to its residential programmes, displays poor throughput. Poor DE throughput contradicts recent advances in educational technologies which provide a range of mitigation and support opportunities through the creation of learning spaces that mediate successful student learning anytime anywhere. This article contributes to the body of knowledge on firstly the disparate profile of Military Academy DE students, and secondly, their disparate access to learning technologies in their working and learning spaces. A survey among DE undergraduates and DE lecturers revealed disparity among respective DE students’ HE-related demographics, and disparity in their access to learning technologies (LT). Resolving disparity in access to LT can mitigate demographic disparity to promote graduate throughput.